Schistosome infection is negatively associated with mite atopy, but not wheeze and asthma in Ghanaian Schoolchildren. Issue 7 (July 2014) - Obeng, B. B.; Amoah, A. S.; Larbi, I. A.; de Souza, D. K.; Uh, H.‐W.; Fernández‐Rivas, M.; van Ree, R.; Rodrigues, L. C.; Boakye, D. A.; Yazdanbakhsh, M.; Hartgers, F. C.
Summary Background Epidemiological evidence suggests that helminth infection and rural living are inversely associated with allergic disorders. Objective The aim of the study was to investigate the effect of helminth infections and urban versus rural residence on allergy in schoolchildren from Ghana. Methods In a cross‐sectional study of 1385 children from urban‐high socio‐economic status (SES), urban‐low SES and rural schools, associations between body mass index (BMI), allergen‐specific IgE (sIgE), parasitic infections and allergy outcomes were analysed. Allergy outcomes were skin prick test (SPT) reactivity, reported current wheeze and asthma. Results Helminth infections were found predominantly among rural subjects, and the most common were hookworm (9.9%) and Schistosoma spp (9.5%). Being overweight was highest among urban‐high SES (14.6%) compared to urban‐low SES (5.5%) and rural children (8.6%). The prevalence of SPT reactivity to any allergen was 18.3%, and this was highest among rural children (21.4%) followed by urban‐high SES (20.2%) and urban‐low SES (10.5%) children. Overall, SPT reactivity to mite (12%) was most common. Wheeze and asthma were reported by 7.9% and 8.3%, respectively. In multivariate analyses, factors associated with mite SPT were BMI (aOR 2.43, 95% CI 1.28–4.60, P = 0.007), schistosome infection (aOR 0.15, 95% CI 0.05–0.41) and mite sIgE (aOR 7.40, 95% CI 5.62–9.73, P < 0.001) but not area. However, the association between mite IgE and SPT differed by area and was strongest among urban‐high SES children (aOR = 15.58, 95% CI 7.05–34.43, P < 0.001). Compared to rural, urban‐low SES area was negatively associated with current wheeze (aOR 0.41, 95% CI 0.20–0.83, P = 0.013). Both mite sIgE and mite SPT were significantly associated with current wheeze and asthma. Conclusion and Clinical Relevance Infection with schistosomes appeared to protect against mite SPT reactivity. This needs to be confirmed in future studies, preferably in a longitudinal design where schistosome infections are treated and allergic reactions reassessed.